Proposal for Alzheimer's diagnosis using molecular buffer and bus network. - Mitatha, S.; Moongfangklang, N.; Jalil, M. A.; Suwanpayak, N.; Saktioto, T.; Ali, J.; Yupapin, P. P. (My University, 2011)
A novel design of an optical trapping tool for tangle protein (tau tangles, β-amyloid plaques) and molecular motor storage and delivery using a PANDA ring resonator is proposed. The optical vortices can be generated and controlled to form the trapping tools in the same way as the optical tweezers. In theory, the trapping force is formed by the combination between the gradient field and scattering photons, and is reviewed. By using the intense optical vortices generated within the PANDA ring resonator, the required molecular volumes can be trapped and moved dynamically within the molecular buffer and bus network. The tangle protein and molecular motor can transport and connect to the required destinations, enabling availability for Alzheimer's diagnosis.